2019
DOI: 10.3390/w11030618
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Climate Change Impacts on River Flows in the Tonle Sap Lake Basin, Cambodia

Abstract: The Tonle Sap is the most fertile and diverse freshwater ecosystem in Southeast Asia, receiving nurturing water flows from the Mekong and its immediate basin. In addition to rapid development in the Tonle Sap basin, climate change may threaten natural flow patterns that sustain its diversity. The impacts of climate change on river flows in 11 sub-basins contributing to the Tonle Sap Lake were assessed using the Soil and Water Assessment Tool (SWAT) model to quantify the potential magnitude of future hydrologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 28 publications
3
28
0
Order By: Relevance
“…Observation‐based studies have reported a shift in flow patterns after the construction of dams (e.g., Räsänen et al, 2012; Sabo et al, 2017; W. Wang et al, 2017); however, these studies have not examined the dynamics of inundation extent, due to data limitations. There has been an increase in model‐based studies in the past decade; however, those studies have focused on some parts of the MRB such as the UMRB (e.g., Dang et al, 2019; Han et al, 2019; Räsänen et al, 2012), Lower MRB (LMRB) (e.g., Dang et al, 2018; Trung et al, 2018), the 3S‐river system (e.g., Wild & Loucks, 2014), Mun river basin (e.g., Akter & Babel, 2012), and TSL and the Mekong Delta regions (e.g., Arias, Piman, et al, 2014; Duc Tran et al, 2018; Minh et al, 2019; Oeurng et al, 2019; Smajgl et al, 2015). There are some basin‐wide modeling studies (e.g., Lauri et al, 2012; Piman et al, 2013; Sridhar et al, 2019; W. Wang et al, 2016), but to the authors' best knowledge, none of those have simulated the inundation dynamics of both natural river‐floodplain systems and manmade‐reservoirs over the entire MRB.…”
Section: Introductionmentioning
confidence: 99%
“…Observation‐based studies have reported a shift in flow patterns after the construction of dams (e.g., Räsänen et al, 2012; Sabo et al, 2017; W. Wang et al, 2017); however, these studies have not examined the dynamics of inundation extent, due to data limitations. There has been an increase in model‐based studies in the past decade; however, those studies have focused on some parts of the MRB such as the UMRB (e.g., Dang et al, 2019; Han et al, 2019; Räsänen et al, 2012), Lower MRB (LMRB) (e.g., Dang et al, 2018; Trung et al, 2018), the 3S‐river system (e.g., Wild & Loucks, 2014), Mun river basin (e.g., Akter & Babel, 2012), and TSL and the Mekong Delta regions (e.g., Arias, Piman, et al, 2014; Duc Tran et al, 2018; Minh et al, 2019; Oeurng et al, 2019; Smajgl et al, 2015). There are some basin‐wide modeling studies (e.g., Lauri et al, 2012; Piman et al, 2013; Sridhar et al, 2019; W. Wang et al, 2016), but to the authors' best knowledge, none of those have simulated the inundation dynamics of both natural river‐floodplain systems and manmade‐reservoirs over the entire MRB.…”
Section: Introductionmentioning
confidence: 99%
“…Siem Reap River is a tributary of the Tonlé Sap (Great Lake) [1]. The Siem Reap River has played a crucial role in supplying the Angkor Temple Complex and the surrounding population for hundreds years.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work by Chim et al (in press) used downscaling of climate change models to show that there is likely to be a continuing, increasing trend in temperatures (max, avg, min), and a decreasing trend in precipitation in the twenty-first century for the upper Siem Reap watershed. Moreover, Oeurng et al [1] undertook an assessment of future climate trends for the tributaries of the Tonlé Sap Basin more broadly, applying three different General Circulation Models (GCMs). They discovered that the future annual average flows (2021-2100) in the Siem Reap River were likely to decrease significantly, from 40 to 70% relative to baseline (1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrological modeling is an effective approach to extrapolate and interpolate missing information over time and space between observations for hydrological assessment [6]. Oeurng et al [7] studied Tonle Sap sub-basin of MRB using the SWAT model. Try et al [8] applied the RRI model for a single flood event in the LMB.…”
Section: Introductionmentioning
confidence: 99%